Evaluating the efficacy of simulation-based training on clinical competency transfer - SARATILA, Iurie; ROMANCENCO, Andrei; SPINEI, Larisa (One Health & Risk Management, 2024)
Introduction. Efficient learning transfer is crucial for training specialists to ensure the provision of quality medical services. This study investigates the impact of simulation-based training on the transfer of medical students’ clinical competencies in parenteral drug administration: subcutaneous (SC), intramuscular (IM), and intravenous (IV). Material and methods. Using a quasi-experimental design, the research incorporates pre- and post-intervention testing, observational assessments, and a satisfaction survey to evaluate the educational impact. Results. The results indicate significant improvements in theoretical knowledge and practical skills post-intervention, with notable score increases for all types of injections (SC: from 50% to 83.33%, IM: from 57.14% to 85.71%, IV: from 42.86% to 85.71%; p<0.001). Similarly, improved clinical performance was demonstrated, highlighting the transferability of the learned competencies to real settings. Student satisfaction recorded a score of 4.71 (95% CI 4.64; 4.79), reflecting strong acceptance and appreciation of the training. Conclusions. The study emphasizes the crucial role of simulation in competency-based medical education, bridging the gap between theoretical knowledge and practical application, and advocates for the systematic integration of simulation into the medical curriculum, suggesting future research directions for optimizing the design and implementation of simulations.